Justice League. Crisis on infinite Earths. Part three [videorecording (Blu-Ray)] - Krieg, Jim; Wolfman, Marv (Warner Bros. Entertainment Inc., 2024)
As the heroes of multiple universes find themselves helpless to stop a wave of destruction destined to wipe out EVERYTHING, they must make a terrible choice: which Earth, if any, will be saved?